2018
DOI: 10.1103/physrevmaterials.2.034003
|View full text |Cite
|
Sign up to set email alerts
|

Electrical valley filtering in transition metal dichalcogenides

Abstract: This work investigates the feasibility of electrical valley filtering for holes in transition metal dichalcogenides. We look specifically into the scheme that utilizes a potential barrier to produce valleydependent tunneling rates, and perform the study with both a kp  based analytic method and a recursive Green's function based numerical method. The study yields the transmission coefficient as a function of incident energy and transverse wave vector, for holes going through lateral quantum barriers oriented … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Valley filters [66,[94][95][96][97][98][99][100][101][102][103][104], serving as valley polarized current generators and allowing only carriers of a specific valley passing through, are one important type of valleytronics devices. Figures 12(a) and (b) depict monolayer and bilayer graphene based two-terminal valley filters, respectively.…”
Section: Valley Filtersmentioning
confidence: 99%
“…Valley filters [66,[94][95][96][97][98][99][100][101][102][103][104], serving as valley polarized current generators and allowing only carriers of a specific valley passing through, are one important type of valleytronics devices. Figures 12(a) and (b) depict monolayer and bilayer graphene based two-terminal valley filters, respectively.…”
Section: Valley Filtersmentioning
confidence: 99%
“…Valley filters are realized in quantum point contact, [6,7] and other structures with nanobubble, [8,9] domain wall, [10,11] Corbino nanodisk [12,13] or Weyl semimetals. [14,15] In addition, mechanical, [16][17][18] optical, [19][20][21] magnetic [22][23][24] and electrical [25][26][27] methods have been applied to process valley information.…”
Section: Introductionmentioning
confidence: 99%
“…While the valley polarization of the charge carriers was extensively studied for bulk monolayers much less attention was paid to its implications on the electronic transport in nanostructures. It has been shown that the valley polarization can be induced in graphene nanoribbons 29 or for hole charge carriers in TMDCs nanostructures 30 by tailoring the shape and potential profile of the structure.…”
Section: Introductionmentioning
confidence: 99%